1977
DOI: 10.1159/000136734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clozapine on the Sleep Pattern in the Rat

Abstract: The effect of clozapine on the sleep pattern in the rat was studied after a single injection (2.5–20 mg/kg) and after daily administration for 11 consecutive days (2 × 20 mg/kg/day). After a single injection clozapine significantly suppressed REM sleep in a dose-related way, leaving slow wave sleep (SWS) unchanged. Following chronic administration, however, clozapine exerted its most prominent effect on SWS, the enhancement of which persisted for at least 3 days after discontinuation of treatment. REM sleep de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
(13 reference statements)
3
7
1
Order By: Relevance
“…In agreement with previous findings (Spierings et al, 1977;Ongini et al, 1993), clozapine promoted non-REM sleep. The present study Clozapine alters sleep-wake behavior S Sorge et al…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous findings (Spierings et al, 1977;Ongini et al, 1993), clozapine promoted non-REM sleep. The present study Clozapine alters sleep-wake behavior S Sorge et al…”
Section: Discussionsupporting
confidence: 93%
“…In rats, clozapine reportedly promotes non-REM sleep and suppresses REM sleep (Spierings et al, 1977;Ongini et al, 1993). However, there is no study that analyzed shortand long-time effects of clozapine on sleep-wake behavior after acute and subchronic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…High-dose risperidone has been shown to inhibit REM sleep as in the study [23]. Clozapine, inconsistent with our findings, has been found to reduce REM sleep but promote non-REM sleep [22]. This discrepancy might be a result of its more complex pharmacological action [48].…”
Section: Discussioncontrasting
confidence: 63%
“…Since the acetylcholine and monoamines are all known to be involved in the regulation of sleep, these drugs are expected to modify the sleep-wake cycle [22,23,24]. Along the sleep-wake cycle, sympathetic and parasympathetic activity fluctuates cyclically, with higher vagal activity during quiet sleep (QS) and higher sympathetic activity during wakefulness and paradoxical sleep (PS) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Polysomnographic studies of sleep-wake patterns in rats have consistently reported that low doses of risperidone increased the amounts of deep slow-wave sleep (dSWS) and decreased both wakefulness and light sleep (ISWS) in rats [11]. Fol-lowing chronic administration in rats, clozapine produced a slight increase of SWS, reduced rapid eye movement (REM) sleep [12,13], and exerted its most prominent effect on SWS [13]. In schizophrenic patients, likewise, it has been reported that risperidone improves sleep quality, sleep continuity, and increases NREM [14], while clozapine may have sleep-inducing properties [15] and olanzapine produces a significant dose-related increase in SWS and sleep continuity in terms of decreased waking [16].…”
Section: Introductionmentioning
confidence: 99%